Not my problem - Smyth, Ciara (Harper Teen, an imprint of HarperCollins Publishers, 2021)
A teen girl, Aideen, makes a journey from self-protectively tough to ready and willing to face her main problem: her single mother's alcoholism
Keywords: Teenage girls / Juvenile fiction; High school students / Juvenile fiction; Children of alcoholics / Juvenile fiction; Secrecy / Juvenile fiction; High school students / Fiction; Lesbians / Fiction; Coming of age / Fiction; Ireland / Fiction; Children of alcoholics; High school students; Secrecy; Teenage girls; Young adult fiction; Bildungsromans; Fiction; Juvenile works; Lesbian fiction; Novels; Jugendbuch